1996
DOI: 10.1128/jvi.70.6.3930-3937.1996
|View full text |Cite
|
Sign up to set email alerts
|

Dengue type 4 virus mutants containing deletions in the 3' noncoding region of the RNA genome: analysis of growth restriction in cell culture and altered viremia pattern and immunogenicity in rhesus monkeys

Abstract: The dengue type 4 virus (DEN4) genome contains a 384-nucleotide (nt) 3 noncoding sequence in which the last 81 nt, predicted to form a secondary structure, are thought to be essential for virus replication. Immediately upstream of the secondary structure, short RNA sequences that are conserved among mosquito-borne flaviviruses have been identified. A series of deletions that range from 30 to 262 nt were introduced into this upstream region of full-length DEN4 cDNA to create viable deletion mutants, some of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(104 citation statements)
references
References 29 publications
6
97
0
1
Order By: Relevance
“…DENV-2 viruses containing single point substitution in the 5 0 UTR exhibited reduced replicative fitness in cellulo and reduced neurovirulence for newborn mice (Leardkamolkarn et al, 2010). This observation was confirmed for several other flaviviruses when deletions were engineered into the 3 0 and 5 0 UTR causing attenuation in cell culture and in animals (Blaney et al, 2010(Blaney et al, , 2008Cahour et al, 1995;Mandl et al, 1998;Men et al, 1996;Zeng et al, 1998). Van Slyke et al (2012) engineered point mutations in the WNV NS5 gene which encodes the RNA polymerase (Van Slyke et al, 2012).…”
Section: Studying Point Mutationsmentioning
confidence: 97%
See 1 more Smart Citation
“…DENV-2 viruses containing single point substitution in the 5 0 UTR exhibited reduced replicative fitness in cellulo and reduced neurovirulence for newborn mice (Leardkamolkarn et al, 2010). This observation was confirmed for several other flaviviruses when deletions were engineered into the 3 0 and 5 0 UTR causing attenuation in cell culture and in animals (Blaney et al, 2010(Blaney et al, , 2008Cahour et al, 1995;Mandl et al, 1998;Men et al, 1996;Zeng et al, 1998). Van Slyke et al (2012) engineered point mutations in the WNV NS5 gene which encodes the RNA polymerase (Van Slyke et al, 2012).…”
Section: Studying Point Mutationsmentioning
confidence: 97%
“…By introducing mutations or constructing intratypic/heterotypic chimeric viruses, numerous virulence determinants have been identified and analyzed to understand the mechanistic basis behind these altered phenotypes (reviews (Hurrelbrink and McMinn, 2003;Mandl, 2005)). Blaney et al (2008Blaney et al ( , 2010, Cahour et al (1995), de Wispelaere and Yang (2012), Huang et al (2005), Hung et al (2004), Leardkamolkarn et al (2010), Matusan et al (2001), Men et al (1996), Modis et al (2004) and Zeng et al (1998); JEV Arroyo et al (2001), Liang et al (2009), Lin et al (2006, Liu et al (2004), Monath et al (2002), Sumiyoshi et al (1995) and Guirakhoo et al (2000Guirakhoo et al ( , 2001Guirakhoo et al ( , 2006, Monath et al (1999Monath et al ( , 2001Monath et al ( , 2003Monath et al ( , 2006, Pugachev et al (2004) and Van Der Most et al (2000); DENV Bray and Lai (1991), Bray et al (1996Bray et al ( , 1998, Caufour et al (2001), Chen et al (1995), Guirakhoo et al (2000Guirakhoo et al ( , 2001Guirakhoo et al ( , 2006 Antivirals DENV Qing et al (2010) and Yang et al (2014) Using an infectious clone of WNV, Pijlman et al (2008) showed that all members of...…”
Section: Host/pathogen Interactionsmentioning
confidence: 99%
“…Various deletions and insertions in the 3= UTR as well as complete deletion of the poly(A) tail may not kill alphaviruses (457)(458)(459), flaviviruses (460)(461)(462), coronaviruses (463)(464)(465), and various plant viruses (466)(467)(468)(469). The repair of the damaged genomes may again involve different mechanisms, including RNA recombination, the use of the viral RdRP-or host-dependent polyadenylation activities, and perhaps some others.…”
Section: Some Additional Lessons From Other Rna Viruses Positive-stramentioning
confidence: 99%
“…1). Mutations disrupting complementarity in any of these elements abrogate viral replication in subgenomic replicon model systems (Alvarez et al, 2008(Alvarez et al, , 2005bBredenbeek et al, 2003;Corver et al, 2003;Friebe and Harris, 2010;Friebe et al, 2011;Khromykh et al, 2001;Lo et al, 2003;Men et al, 1996;Villordo et al, 2010;Zhang et al, 2008), while compensatory mutations rescue viability (Alvarez et al, 2008(Alvarez et al, , 2005bFriebe and Harris, 2010;Friebe et al, 2011;Khromykh et al, 2001;Lo et al, 2003;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%